ORNAC SEEKS FEDERAL INCORPORATION - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 2006)
Operating Room Nurses Association of Canada (ORNAC) has recently begun the process of applying for Federal Incorporation. Based on recommendations from the finance committee and ORNAC’s legal advisors the Executive and Board have retained professional legal services to assist with the application process.